Literature review on Mud therapy - Sivalathajini, V.; Sounthararajan, K. (Trincomalee Campus, Eastern University, 2016)
Historically, Mud therapy is the treatment has been used for centuries in Fastern and Western countries. It is a type of treatment, mud is one of five elements of nature having immense impact on the body in health as well as in sickness, It can be employed conveniently as therapeutic agent in many diseases. The objective of this study the growing interest caused by the mud therapy in indigenous medicine, employed to free interference in body, interference field it's an area on the body that tests abnormally as a results of individual of multiple factors. Such as Scars, Nutritional deficiencies, metal toxicity, Contusion and other skin affections. Data was gathered from Siddha, Traditional, Western medical books, Journals and internet. Mud retains moisture for a long time. when applied over the body part it causes cooling and its shape, consistency can be changed easily by adding water. Mud procured for treatment purpose should be black cotton soil with greasiness and free from pollution and contamination. Mud once purified, comes in to diverse usage and applications like bathing with mud, sleeping or walking bare foot in mud, mud massage. Mud therapy uses in five ways, mud pack, mud massage, mud nap, mud bath, and mud walk. Most imperative usage of the mud therapy is the application of mud packs. Scrubbing the skin mildly with mud helps to overhaul skin tissues and improves on the working of body organs rendering good blood circulation in the same, where thermal mud that contains high concentrations of minerals are spread over the body help cleanse, purify and revitalize the skin. Many health benefits in mud therapy as acne and pimples, digestive aid, constipation, diarrhoea, vomiting, eye maladies, skin affections, headache, fever, remedy of skin, for skin glow, healing benefit. anti-aging, for stress relief.
Keywords: Mud therapy; Indigenous medicine; Application